2019
DOI: 10.1038/s41598-019-53243-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-cleanable, waterproof, transparent, and flexible Ag networks covered by hydrophobic polytetrafluoroethylene for multi-functional flexible thin film heaters

Abstract: We demonstrate a self-cleanable, waterproof, highly transparent, and flexible Ag network covered by a very thin transparent polytetrafluoroethylene (PTFE) layer using typical magnetron sputtering for multi-functional flexible thin film heaters used in smart windows. By passivation of the self-assembled Ag network with very thin PTFE films, we fabricated a multi-functional Ag network suitable for flexible thin film heaters. At a PTFE thickness of 10 nm, the Ag network passivated by hydrophobic PTFE layer showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…To develop more useful transparent heaters for practical applications, it is necessary to consider the droplet evaporation characteristics and wettability control on the surface of the transparent conductor-based heaters. Kim et al demonstrated that a multifunctional transparent heater with a flexible silver nanowire network covered by a vacuum-sputtered polytetrafluoroethylene layer produced a self-cleaning, waterproof, and highly transparent surface. , In addition, Kulkarni et al reported that the surface wettability of the transparent conductor could be modified by adsorbing a monolayer of 1-hexadecanethiol on the Ag wire mesh surface . However, a few studies have been performed; thus, research on high-performance transparent heaters with controlled surface wettability is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…To develop more useful transparent heaters for practical applications, it is necessary to consider the droplet evaporation characteristics and wettability control on the surface of the transparent conductor-based heaters. Kim et al demonstrated that a multifunctional transparent heater with a flexible silver nanowire network covered by a vacuum-sputtered polytetrafluoroethylene layer produced a self-cleaning, waterproof, and highly transparent surface. , In addition, Kulkarni et al reported that the surface wettability of the transparent conductor could be modified by adsorbing a monolayer of 1-hexadecanethiol on the Ag wire mesh surface . However, a few studies have been performed; thus, research on high-performance transparent heaters with controlled surface wettability is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…A flexible and transparent conductive electrode (FTCE) is a thin film with high transparency, high conductivity, and outstanding flexibility [1][2][3]. Due to the rapid advancements in flexible electronics and wearable devices, FTCEs have gained a great deal of attention as a key component of flexible displays [4][5][6], flexible touch panels [7][8][9], flexible thin film heaters (TFHs) [10][11][12][13][14][15][16], photoelectric devices [17][18][19][20], and wearable electronics [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…summarized the characteristics of electrode materials used in TFH . Recently, our group has also studied various materials, such as the AgNW network, self-assembled network, W-doped In 2 O 3 , and MoO 3 –Ag–MoO 3 . Despite the high electrical and thermal conductivities of AgNW, AgNW-based transparent conductors are easily oxidized in air, have low heat and oxidation resistance, and have a rough surface. , Furthermore, TFH electrode materials were studied through a large-area roll-to-roll process with CuO x –Cu–CuO x , InZnSiO–Ag–InZnSiO, ZnSnO–AgPdCu–ZnSnO, ITO–Cu–ITO, and ITO–Ag–ITO. Although nanoparticle-based oxide electrode such, as InZnO, InZnSnO, InTiO, and InSnO has been reported, research into solution-based ITO conductors and solution-multilayers for transparent TFHs is still insufficient. Specifically, studies on the crystallinity, preferred orientation, and electrical and optical properties depending on the thickness of the sputtered ITO have been conducted; however, for the outstanding electrical and optical properties of ITO NPs, studies on optimizing the thickness and annealing process have not been sufficiently performed.…”
Section: Introductionmentioning
confidence: 99%